Cholangiocarcinoma: Current Knowledge and New Developments - Blechacz, Boris (Gut and liver, 2017)
Cholangiocarcinoma (CCA) is the second most common primary malignancy. Although it is more common in Asia, its incidence in Europe and North America has significantly increased in recent decades. The prognosis of CCA is dismal. Surgery is the only potentially curative treatment, but the majority of patients present with advanced stage disease, and recurrence after resection is common. Over the last two decades, our understanding of the molecular biology of this malignancy has increased tremendously, diagnostic techniques have evolved, and novel therapeutic approaches have been established. This review discusses the changing epidemiologic trends and provides an overview of newly identified etiologic risk factors for CCA. Furthermore, the molecular pathogenesis is discussed as well as the influence of etiology and biliary location on the mutational landscape of CCA. This review provides an overview of the diagnostic evaluation of CCA and its staging systems. Finally, new therapeutic options are critically reviewed, and future therapeutic strategies discussed.